Penerapan Slow Deep Breathing Exercise Terhadap Nyeri Selama Pelepasan Water Seal-Drainage (Wsd) Pada Pasien Pneumothorax Di Ruang Flamboyan 7 Rsud Dr. Moewardi Surakarta - Lisa Aryanti; Eska Dwi Prajayanti; Isti Wulandari (STIKes Ibnu Sina Ajibarang, 2024)
Background : The lung health problem pneumothorax is a health problem that threatens lung health caused by air entering the chest cavity and specifically the pleural cavity. The problem of removing the WSD tube causes pain due to the output of a foreign object, causes pain due to the output of a foreign object producing unpleasant feelings such as pain. Non-pharmacological techniques are used to reduce pain, namely using slow deep breathing therapy where is a release of endorphin neurotransmitters which have an effect on reducing pain. Purpose: to find out the results of applying slow deep breathing exercise therapy to reduce pain during WSD release. Method: Case study. Sample of 2 respondents with 1 control respondent and 1 intervention respondent. The research instruments used educational media, leaflers and slow deep breathing exercise intervention learning videos as well as pain measurement instruments using the visual analogue scale (VAS), namely to measure participants pain intensity before (pre) intervention and after (post) slow deep breathing exercise intervention. Results: respondent experienced a decrease in pain intensity from moderate intensity to light intensity, the decrease in pain intensity in the control grup (Tn. A), decreased less than the intervention group (Tn. L) with a difference of two on the pain scales decreasing more Conclusion: there is a difference in pain intensity after slow deep breathing exercise therapy.